Mystical Hunger: Memaknai Lapar dalam Teologi Mistik sebagai Upaya Transformasi Sosial - Leksmana Leonard (Indonesian Journal of Theology, 2020)
This article endeavors to discuss hunger as a site for mystical encounter with God. The history of Christian mysticism shows that our experiences play a significant role in the sourcing of its very theology. Upon consideration of a clarifying definition for mystical theology, I elaborate on Simone Weil’s view of hunger as mystical experience along with Dorothee Sölle’s notion that mystical experience impacts social transformation. With help from both, hunger can be seen as an experience of intimacy with God and at once possesses the dimension for hospitality, for the purposes of breaking down social barriers.